Young adult cannabis use and circulating endocannabinoid concentrations on cognitive performance - Wallace, Alexander L.; Baca, Rachel; Andrade, Gianna; Hillard, Cecilia J.; Happer, Joseph P.; Wade, Natasha E.; Courtney, Kelly E.; Hernandez Mejia, Margie; Jacobus, Joanna (Frontiers in Adolescent Medicine, 2025)
IntroductionThe endocannabinoid (eCB) system is a regulatory mechanism that helps to maintain homeostasis in the brain. Cannabis use and circulating eCB disruptions have been linked with altered memory; however, this work has largely been done in animal models with minimal investigation into these relationships by sex. We aim to investigate how circulating eCB concentrations in cannabis using young adults are associated verbal memory. We hypothesize that greater amounts of self-reported cannabis use and lower eCB circulating concentrations will be associated with worse learning and memory. Sex as a potential moderator was explored.MethodEighty-seven participants between the ages of 18–20 (63% female) completed measures on past 30-day cannabis use, verbal learning and memory (Rey Auditory Verbal Learning Task; RAVLT), and a blood draw. Serum sample analysis from blood draws assessed concentrations of the eCBs 2-arachidonoylglycerol (2-AG) and N-arachidonoylethanolamine (AEA). Linear regressions examining cannabis group status based on past 30 day cannabis use [no use, light use (<8 use days), and heavy cannabis use (≥8 use days)], eCB concentrations, and their interaction on RAVLT learning and memory scores. Three-way sex by cannabis status by eCB concentrations interactions were also explored.ResultsHeavy cannabis use was associated with worse verbal memory performance. Significant interactions between 2-AG and heavy cannabis use were observed, revealing that individuals with elevated 2-AG concentrations and heavy cannabis use showed better performance on verbal learning and memory tasks. In contrast, heavy cannabis use with higher AEA concentrations performed worse on verbal learning tasks. There was a significant three-way interaction with sex, cannabis use group, and 2-AG concentrations on verbal learning where men with heavy cannabis use and high 2-AG concentrations had better verbal learning compared to men with lower 2-AG concentrations.DiscussionDistinct patterns emerged between 2-AG and AEA concentrations and memory performance among individuals with heavy cannabis. Higher 2-AG concentrations and lower AEA concentrations correlated with improved memory performance in the heavy cannabis use group, suggesting that circulating eCB profiles may serve as a biomarker for cannabis-related cognitive deficits. More work is needed to disentangle the complex relationships between circulating eCB concentrations, cannabis use, and neurocognitive functioning.